Inconsistency in asylum appeal adjudication - Gill, N; Rotter, R; Burridge, A; Griffiths, M; Allsopp, J (Refugee Studies Centre, University of Oxford, 2015)
New research findings indicate that factors such as the gender of the judge and of the appellant, and where the appellant lives, are influencing asylum appeal adjudication.